Boosting the energy-storing performance of hydrothermally synthesized ZnO by MnTe for supercapacitor applications - Zahra, Tehreem; Alotaibi, B. M.; Alrowaily, Albandari W.; Alyousef, Haifa A.; Al-Sehemi, Abdullah G.; Aman, Salma (Journal of materials science. Materials in electronics, 2024)
Energy scarcity and environmental deterioration are the two main issues the world is currently experiencing. Because of their increased energy/power density and longer cycle lifetimes, pseudocapacitors have recently gained the interest of researchers in energy sector. In this study, a novel hierarchical ZnO/MnTe nanocomposite was synthesized by hydrothermal procedure for application in supercapacitors. The physical properties of the newly created electrode material were investigated using a variety of techniques. According to the outcomes of electrochemical investigations, ZnO/MnTe showed specific capacitance ( C sp ) of 1461 F g −1 , specific energy ( S E ) of 54 Wh kg −1 , a specific power ( S P ) of 267 W kg −1 at current density ( J d ) of 1 A g −1 , and cyclic constancy even after 5000th cycle in 2-M KOH due to combined effect of binary metals dichalcogenides. ZnO/MnTe exhibited enhanced electrochemical characteristics owing to variable oxidation state of Zn and Mn, enhanced electrical conductivity, small crystallite size, and augmented specific surface area (SSA) for storage of more charges. This study reveals the significant potential of the ZnO/MnTe electrode as a viable option for supercapacitors and other energy-conserving devices, such as capacitor and batteries.